Millennial monsters : Japanese toys and the global imagination - Allison, Anne, 1950- (Asia--local studies/global themes, 2006)
From sushi and karaoke to martial arts and technoware, the currency of made-in-Japan cultural goods has skyrocketed in the global marketplace during the past decade. The globalization of Japanese "cool" is led by youth products: video games, manga (comic books), anime (animation), and cute characters that have fostered kid crazes from Hong Kong to Canada